Wide‐range, high‐precision and low‐complexity MPPT circuit based on perturb and observe algorithm. Issue 16 (1st August 2017) - Jiang, Rucheng; Han, Yan; Zhang, Shifeng
Abstract : A novel CMOS maximum power point (MPP) tracking circuit with high‐power throughput, high‐tracking efficiency and low complexity for solar converters is presented. The power acquisition circuit guarantees the tracking efficiency and the control logic module which implements the multiplexing of power conversion, power storage and power comparison, simplifies MPPT circuit significantly. Simulation and measurement results show that the MPPT circuit operates properly and the tracking efficiency stays larger than 99.9% with the output current of the power acquisition circuit varying from 5 to 100 μA